Strategic Information Moderated By Effectiveness Management Accounting Information Systems: Business Strategy Approach - Lilis Puspitawati (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2021)
The industrial revolution 4.0 increases business competition and the increasing need for accounting information for strategic decision making. Accounting information is financial information needed by managers to predict and determine the company's strategic policies in the future, however, the current condition of many companies has not been able to produce quality accounting information which has an impact on the production of inappropriate financial policies. This study aims to determine how much the business strategy affects the effectiveness of the use of accounting software and how much the effectiveness of accounting software affects the quality of accounting information. The population in this study were 472 managers of state-owned companies and a total sample of 312 managers of BUMN which were determined by simple random sampling technique. Testing data using covariance-based structural equation modeling (SEM) with Lisrell software. The results of this study prove that State-Owned Enterprises in Indonesia effective application software affects quality accounting information, as well as the company's business strategy affects the effectiveness of accounting software.